Estimation of cardiac QTc intervals in people prescribed antipsychotics: a comparison of correction factors - Teodora Andric; Karl Winckel; Timothy David Tanzer; Samantha Hollingworth; Lesley Smith; Katherine Isoardi; Olivier Tan; Dan Siskind (SAGE Publishing, 2022)
Background: A prolonged electrocardiogram (ECG) QT interval is associated with cardiac events and increased mortality. Antipsychotics can prolong the QT interval. The QT interval requires correction (QTc) for heart rate using a formula or QT-nomogram. The QT and QTc can be calculated automatically by the ECG machine or manually; however, machine-measured QT(c) intervals may be inaccurate. Objective: We aimed to investigate the mean QTc and proportion of prolonged QTc intervals in people taking antipsychotic medicines. Methods: We conducted an observational retrospective chart review and data analysis of all consecutive patients taking antipsychotics, with an ECG record, admitted to the psychiatric unit of a large tertiary hospital in Brisbane, Australia, between 1 January 2017 and 30 January 2019. We investigated the mean QTc of people taking antipsychotics to determine differences using (a) machine versus manual QT interval measurement and (b) QTc correction formulae (Bazett, Fridericia, Framingham, Hodges and Rautaharju) and the QT-nomogram. We also determined the number of people with a prolonged QTc using different methods and compared rates of prolonged QTc with antipsychotic monotherapy and polypharmacy. Results: Of 920 included people, the mean (±SD) machine-measured, Bazett-corrected QT interval (recorded from the ECG) was 435 ms (±27), significantly longer ( p  < 0.001) than the mean manually measured corrected QT intervals with Fridericia 394 ms (±24), Framingham 395 ms (±22), Hodges 398 ms (±22) and Rautaharju 400 ms (±24) formulae. There were significantly more people with a prolonged QTc using machine-measured QT and the Bazett formula (12.0%, 110/920) when compared with manually measured QT and the Fridericia formula (2.2%, 20/920) or QT-nomogram (0.7%, 6/920). Rates of QTc prolongation did not differ between people taking antipsychotic polypharmacy compared with monotherapy. Conclusion: Machine-measured QTc using the Bazett formula overestimates the QTc interval length and number of people with a prolonged QTc, compared with other formulae and the QT-nomogram. We recommend manually measuring the QT and correcting with the Fridericia formula or QT-nomogram prior to modifying antipsychotic therapies.